Lymphopenia predicts poor outcomes in newly diagnosed multiple myeloma - Grace M. Ferri; Cenk Yildirim; Nhan V. Do; Mary Brophy; Joseph S. Park; Nikhil C. Munshi; Nathanael R. Fillmore; Camille V. Edwards (Blood Advances)
Abstract: Bone marrow microenvironment plays an important role in promoting growth and survival of multiple myeloma (MM) cells. The tumor-promoting immune microenvironment is augmented while antitumor immune responses are inhibited. Although clinical and genomic markers of high-risk MM have been described, the immune status is just being recognized as a potential mediator of disease behavior. This is even more important with the development of a number of immune-based therapies. Based on these considerations, we evaluated peripheral blood absolute lymphocyte count (ALC) as an easily accessible marker representing immune microenvironment at diagnosis and after treatment of MM. We retrospectively evaluated 11 427 patients diagnosed with MM between 2000 and 2019 at Veterans Administration hospitals using ALC obtained closest to diagnosis and up to 2.5 years thereafter. Patients were stratified into 3 ALC categories: severely low, low, and normal (<1 × 103/μL, 1 × 103/μL to 1.5 × 103/μL, and >1.5 × 103/μL, respectively). Lymphopenia (including severely low and low ALC) was present in 53% of patients at MM diagnosis and was associated with inferior overall survival (OS). The median OS for patients with severely low, low, and normal ALC at diagnosis was 2.7, 3.3, and 4.2 years (P < .001), respectively. Moreover, persistent or new development of lymphopenia during treatment and follow-up was also associated with inferior OS. Our findings support the use of ALC as a biomarker for risk stratification in MM.